Precalculus: Functions and Graphs - A. Barnett Raymond (MC Graw Hill, 2001)
This book would be around 200 pages shorter if it omitted all of the graphing calculator applications, which it should. There are questions asking students to describe the shape, or find the range, of a function by plotting it on a graphing calulator. As a pedagogical exercise, this is useless. It's also counterproductive from the perspective of instructors faced with the unenviable task of teaching students to graph functions and find their ranges algebraically. Although the emphasis of a precalculus class should not be overly theoretical, students should come out of it with some notion of what sorts of operations are mathematically and logically sound. Finding the range of a function by plotting it on a calculator is not, while completing the square of a quadratic and analyzing it is. The book presents these two methods on equal footing.